The invisible invasion - Brady, Dustin; Brady, Jesse (Kansas City, Missouri : Andrews McMeel Publishing, 2018)
When Mark is sucked into the game "Go Wild", he becomes invisible which makes it that much harder for Jesse to find him.
Keywords: Video games -- Juvenile fiction; Friendship -- Juvenile fiction; Invisibility -- Juvenile fiction; Adventure stories; Video games -- Fiction; Friendship -- Fiction; Video games -- Juvenile fiction; JUVENILE FICTION / Action & Adventure; JUVENILE FICTION / Boys & Men; JUVENILE FICTION / Reader - Intermediate; Adventure stories; Friendship; Invisibility; Video games; Action and adventure fiction; Fiction; Juvenile works; Science fiction; Action and adventure fiction; Science fiction